Dimensionamento e análise computacional de um galpão metálico utilizando o software SAP 2000 - PINHEIRO, Bianca Saldanha (2023)
The present study presents a tutorial of the SAP 2000 structural analysis program for modeling, dimensioning and structural analysis of a building with structure in metallic profiles. SAP 2000 is software for structural analysis that uses the finite element method, developed by the American company CSI - Computer & structures Inc. and marketed in Brazil by the company Múltiplos Softwares Técnicos in. The software is widely used to analyze small, medium and large buildings, however, despite being an important analysis and dimensioning tool, it is noted the difficulty of civil engineering students in learning to use it, as well as the shortage of material in Portuguese didactically presenting tutorials to assist in the use of the program, since, as structures evolve, becoming more and more complex, in most situations, resolution by means of calculations analytical. In this way, the present work aims to contribute to reduce these difficulties, presenting a manual of modeling, dimensioning and analysis of metallic structure, in order to generate the adequate profile for each bar, as well as the diagrams of efforts, deflections, shear, reactions and deformed